Physical Inactivity, Sedentary Behavior and Chronic Diseases - Marquez-Andrade, J (Korean Journal of Family Medicine, 2017)
New research into physical activity suggests that it is no longer sufficient just to meet minimum levels recommended by health guidelines in order to reduce cardiovascular risk. Both physical inactivity and sedentary behavior have their own health hazards and need to be addressed separately, in order to explore their different deleterious mechanisms. The aim of this review was to define and to characterize both concepts, and their relationship with major non-communicable chronic diseases. A PubMed database search was undertaken, using the following key words: physical activity, physical inactivity, sedentarism, sedentary behavior, and non-communicable chronic disease. This literature review provides an updated view on physical inactivity and sedentary behavior, and reevaluates their prevalence and association with major non-communicable chronic disease. © 2017 The Korean Academy of Family Medicine.